Comparative Genomic and Phylogenomic Analyses Clarify Relationships Within and Between Bacillus cereus and Bacillus thuringiensis: Proposal for the Recognition of Two Bacillus thuringiensis Genomovars - Baek, Inwoo; Lee, Kihyun; Goodfellow, Michael; Chun, Jongsik (Frontiers in Microbiology, 2019)
The present study was designed to clarify the taxonomic status of two species classified as Bacillus cereus sensu lato, namely B. cereus sensu stricto and Bacillus thuringiensis. To this end, nearly 900 whole genome sequences of strains assigned to these taxa were the subject of comparative genomic and phylogenomic analyses. A phylogenomic tree based on core gene sequences showed that the type strains of B. cereus and B. thuringiensis formed a well-supported monophyletic clade that was clearly separated from corresponding clades composed of the remaining validly published species classified as B. cereus sensu lato. However, since average nucleotide identity and digital DNA–DNA hybridization similarities between the two types of Bacillus were slightly higher than the thresholds used to distinguish between closely related species we conclude that B. cereus and B. thuringiensis should continue to be recognized as validly published species. The B. thuringiensis strains were assigned to two genomically distinct groups, we propose that these taxa be recognized as genomovars, that is, as B. thuringiensis gv. thuringiensis and B. thuringiensis gv. cytolyticus. The extensive comparative genomic data clearly show that the distribution of pesticidal genes is irregular as strains identified as B. thuringiensis were assigned to several polyphyletic groups/subclades within the B. cereus–B. thuringiensis clade. Consequently, we recommend that genomic or equivalent molecular systematic features should be used to identify B. thuringiensis strains as the presence of pesticidal genes cannot be used as a diagnostic marker for this species. Comparative taxonomic studies are needed to find phenotypic properties that can be used to distinguish between the B. thuringiensis genomovars and between them and B. cereus.